The possible benefits of reduced errors in the motor skills acquisition of children - Capio Catherine M; Sit Cindy HP; Abernethy Bruce; Masters Rich SW (BMC, 2012)
Abstract An implicit approach to motor learning suggests that relatively complex movement skills may be better acquired in environments that constrain errors during the initial stages of practice. This current concept paper proposes that reducing the number of errors committed during motor learning leads to stable performance when attention demands are increased by concurrent cognitive tasks. While it appears that this approach to practice may be beneficial for motor learning, further studies are needed to both confirm this advantage and better understand the underlying mechanisms. An approach involving error minimization during early learning may have important applications in paediatric rehabilitation.